Pemanfaatan Limbah Karbit Pada Campuran Beton Ringan Sebagai Bahan Tambah - ERDIANSYAHPUTRA, B; SHARWANDA ASFARINA (AGREGAT, 2024)
Lightweight concrete is a rapidly developing technology. It is utilized for a variety of applications, including construction walls, insulation, roofing, and foundation fillers. Because of its low density and energy consumption, lightweight concrete may replace traditional concrete materials, encouraging low-carbon growth. The purpose of this study is to determine the effect of adding carbide waste to the concrete mix composition, as well as to discover the concrete mix that produces the best outcomes. The method is carried out in the form of determining the materials and composition of the mixture to be used, variations in the composition of the mixture with a percentage of 0-35 porsen carbide waste with a ratio of 1Pc: 6Sand, and one variation will be made three test objects and inspected at the age of 7, 14, and 28 days. Making samples involves creating lightweight concrete test items with predetermined composition changes. test items in the shape of 5x5x5 cm cubes. The results showed that the average compressive strength of concrete from a mixture of 0%, 15%, 20%, 25%, 30%, and 35% variation of carbide waste at the age of 28 days was 6.35 MPa, 5.50 Mpa, 5.45 Mpa, 5.32 Mpa, and 4.78 Mpa, and the content weight was 1872.12 kg/m3, 1865.76 kg/m3, 1862.31 kg/m3, 1853.42 kg/m3, 1840. 24 kg/m3, and 1808. 26 kg/m3. The optimal compressive strength of 28-day-old concrete with 15% carbide waste was 5.50 MPa when using a 1Pc:6Psr concrete mix.